Family Caregiver’s Quality of Life of Elderly Parent with Alzheimer’s Disease - Michael Dirk Roelof Maitimoe; Magdalena S. Halim (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
This research explores the relationship between burden of care, health perception, and demographic as aspects that affecting the quality of life of 50 family caregivers with the mean of age is 46.68 years old and SD = 12.97. Each subject has been given QoL-AD, HPQ, and ZBI-22, then being analyzed with Pearson Correlational Analysis and Multiple Regression Analysis with the stepwise method. The result showed that burden of care (r = - .454, p < .01), current health (r = .660, p < .01) and history of AD (r = .339, p < .05) significantly related to quality of life, while regression analysis shows that current health and AD history as a significant contributor (R2 = .496, p < .01) Furthermore, it is necessary to test the model with more diverse variables that significantly contributed to family caregivers’ quality of life.